The Use of Student Worksheets on Arabic Learning Outcomes / Istikhdām Waraqah al-Tadrībāt ‘Alā Natījah Ta’allum al-Lughah al-Arabiyyah - Hikmah Nur Fitriani (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2021)
This research aims to know the effectiveness of using the worksheet student on learning Arabic and revealing the motivating and obstacle factors for eighth-grade students at Darul Ulum Islamic Junior High School Ngaliyan Semarang. The type of this research is descriptive qualitative research. The researcher calculated using simple symbols to know the worksheet student's effectiveness by the student's results in the final exam. As a result of this research, the percentage of the successful student in the 8th grade "A" is 11.5 percent, and the student who has not achieved the minimum completeness criteria is 88.4%. The percentage of the successful student in the 8th grade “B” is 4%, and the student who has not achieved the minimum completeness criteria is 96%. And the 8th grade "C," there is no student who has completed minimum completion. Therefore, from the data of the previous three chapters, it is indicated that the high percentage of students who did not pass and the lower percentage the successful student. The researcher considers that using the exercises sheet on the result of learning the Arabic language at Dar Al Ulum Islamic Junior High School Ngaliyan Semarang is ineffective. The success of learning depends on using the worksheet student and many factors that affect the result of learning in terms of objectives, educational method, teacher, students, material, teaching aids, and everything that defends education to obtain success. Keywords: Learning Arabic, Result of Learning, Worksheet Student. الملخص يهدف هذا البحث لمعرفة فعالية استخدام ورقة التدريبات على نتيجة تعلم اللغة العربية وكشف العوامل الدافعة والعائقة في استخدام ورقة التدريبات في تعليم اللغة العربية لدى طلاب الصف الثامن بمدرسة دار العلوم المتوسطة الإسلامية سمارانج. نوع هذا البحث هو البحث الوصف الكيفي. وقامت الباحثة بإجراء العمليات الحسابية باستخدام الرموز البسيطة لمعرفة فعالية استخدام ورقة التدريبات بنتيجة الامتحان في آخر السنة الدراسية. ونتيجة هذا البحث نسبة الطالب الناجح في الفصل الثامن أ هي 11,5 بالمائة، والطالب الذي لم يحصل على الكمال حد الأدنى هو 88,4 بالمائة. ونسبة الطالب الناجح في الفصل الثامن ب هي 4 بالمائة، والطالب الذي لم يحصل على الكمال حد الأدنى هو 96 بالمائة. وأما في الفصل الثامن ج فلا طالب الذي حصل على كمال حد الأدنى. فلذلك، من بيانات ثلاثة فصول السابقة تدل أن النسبة المئوية المرتفعة على الطالب الذي لم ينجح وبالنسبة المئوية السفيلة على الطالب الناجح. تعتبر الباحثة أن استخدام ورقة التدريبات على نتيجة تعلم اللغة العربية بمدرسة دار العلوم المتوسطة الإسلامية نجاليان سمارانج غير فعال. ليس نجاح التعليم من ناحية استخدام ورقة التدريبات فقط، ولكن كثيرا من العوامل التى تؤثر على نتيجة التعليم من ناحية الأهداف والطريقة التعليمية والمدرس والطلاب والمادة والوسائل التعليمية وكل ما يدافع التعليم للحصول على النجاح. الكلمات الرئيسية: ورقة التدريبات، نتيجة التعلم، تعليم اللغة العربية.